Designing and Developing the Comprehensive Monitoring of Public Policies Adopted by Islamic Consultative Assembly with the Emphasis on the Field of Economic Affairs - Karimian, Omid; Hosseinpour, Davoud; Zadeh, Fattah Sharif; Noori, Roohallah (International Review of Management and Marketing, 2017)
Understanding the way of performance of the mechanism and successfulness of government policies approved by supreme institutions of the International Research Institute (IRI) have always been challenging. The aim of the present study is to design and develop the comprehensive monitoring of public policies adopted by Islamic consultative assembly with the emphasis on the field of economic affairs. Elements of Zahariadis’ model (1998) and other theories explaining factors affecting realization of public policies were employed as the basics of the analysis model of public policies approved by Majlis and prediction and development of a monitoring model. The research population consists of all current and previous members of the parliament (MPs) in the Commissions of Plan and Budget Calculations, Article 90, Economy and Industry and Executives Audit Court and the Organization of Management and Planning. They included 574 MPs. The study uses a mixed method research (qualitative and quantitative research). The research methods used in the qualitative research are “documentary research and Delphi method” and in the quantitative part the survey research method was employed so that using the extracted data and the Delphi method, the main questionnaire was developed and used in the form of a researcher-made questionnaire. In addition, to determine the sample size, the Cochrane’s formula was employed. The sample size was determined to consist of 130 participants. According to the results obtained from the commonalities table, the factor analysis technique was deemed appropriate. The eigenvalue in the total variance table for three factors was bigger than 3; therefore, the number of extracted factors suggested for the model was estimated as three using the factor analysis technique. Then questions were classified into three main factors as follows: (1) Policymaking strategies, (2) policymaking and (3) monitoring strategies. Using the mentioned factors, the causal and structural conditions governing the public policies of the IRI approved by Majlis in the field of economic affairs from 2004 to 2014 can be explicated. The political conclusion of the present stud is that paying attention to main strategies of the IRI approved by expediency council under the supervision of the supreme leader and the compatibility of public policies approved by Majlis in the economic affairs with development plans of the IRI are inevitable. Moreover, establishing a kind of coordination and unity among ideas and policies of the government and Majlis with respecting the independence of each side should be main elements of the system of monitoring the good performance of public policies approved by Majlis. Keywords: Public Policies, Monitoring Models, Majlis, Economic Affairs JEL Classification: Z18